MODELO DE GESTÃO PARA INCUBADORAS DE EMPRESAS SOB APERSPECTIVA DE METODOLOGIAS DE GESTÃO APOIADAS EM REDE SOB A CONFIGURAÇÃO DA HÉLICE TRÍPLICE: O CASO DA INCUBADORA DE EMPRESAS DE BASE TECNOLÓGICA DA UFF - Ribeiro, Ana Cristina Silva (2006)
Incubators are becoming a global phenomenon on optimization and consolidation enterprise development support. At this universe the success of a management model depends on both Incubator and Incubated Enterprise success. This work presents an analysis of Technological Base Enterprises Incubator of UFF management model. It intends to show the Incubator career, goal and specific setting, so that enable incubator processes and services continued improvement. The models of Knowledge Management, Triple Helix and Balanced Scorecard will be used as theoretical support for the analyses. At the end the principal management handicaps are presented together with suggestions for communication, operational instruments and management processes improvement.